MAGNESIUM IN THE DYNAMICS OF CARBOHYDRATES AND ANTIOXIDANT METABOLISM OF COFFEE SEEDLINGS IN TWO IRRADIANCE LEVELS - Dias, Kaio Gonçalves de lima; Guimarães, Paulo Tácito Gontijo; Furtini Neto, Antônio Eduardo; Faquin, Valdemar; de Pádua, Eduane José; de Silveira, Helbert Rezende Oliveira (Coffee Science - ISSN 1984-3909, 2018)
The aim of this study was to verify the physiological impacts and the carbohydrate dynamics of Coffea arabica, seedlings subjected to increasing concentrations of magnesium (Mg) and two irradiance levels. Methods: The experiment was carried out in growth chambers with nutrient solution. The treatments were five concentrations of Mg (0, 48, 96, 192, and 384 mg L-1) and two irradiance levels (80 and 320 μmol of photons m-2 s-1). The coffee seedlings were under the treatments for 90 days. Results: The leaves with deficiency or excess of Mg exposed to the irradiance of 320 μmol of photons m-2 s-1 accumulated more carbohydrates than those exposed to 80 μmol of photons m-2 s-1. The accumulation of carbohydrates in the leaves increased the activity of antioxidant enzymes due to the increased production of reactive oxygen species (ROS). Leaves exposed to 320 μmol of photons m-2 s-1 exhibited symptoms of scald by the sun caused by photo-oxidation. The scald was more intense in plants with abnormal concentrations of Mg. The antioxidant system of the coffee tree is closely relates to the Mg supply and irradiance levels. Concentrations of Mg between 48 and 96 mg L-1 functioned as a mitigating agent of oxidative stress under stressful conditions caused by high irradiance level.